2018
DOI: 10.1002/aic.16153
|View full text |Cite
|
Sign up to set email alerts
|

Product design: A pricing framework accounting for product quality and consumer awareness

Abstract: A systematic framework has been developed to determine the optimal price of a completely new (or existing but improved) chemical product that is being launched (or relaunched) in the presence of a competing product. It has four elements. The first is a pricing model derived from a utility function with constant elasticity of substitution. It accounts for consumers' awareness of the product under consideration and consumer preferences. The second is a set of relationships relating the consumer preferences and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…In the case of formulated products, many of the methodologies consider an interdisciplinary approach, where aspects such as product properties, marketing, costs, management, and process design are combined or at least mentioned when presenting a design methodology 137,142,143,153 . Formulated products are frequently found in the consumer market, thus the inclusion of multiple variables and the application of interdisciplinary knowledge is necessary for their design 59,122,123 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of formulated products, many of the methodologies consider an interdisciplinary approach, where aspects such as product properties, marketing, costs, management, and process design are combined or at least mentioned when presenting a design methodology 137,142,143,153 . Formulated products are frequently found in the consumer market, thus the inclusion of multiple variables and the application of interdisciplinary knowledge is necessary for their design 59,122,123 …”
Section: Resultsmentioning
confidence: 99%
“…The second most repeated combination is the one that includes the phases of needs analysis, alternatives proposition, and alternatives selection, with 24 publications (11%). These publications correspond to the methodologies addressing both problem definition and problem solving, where the customer needs become an important constraint for the design 59,122,123 . Product design methodologies that include the process design phase are not commonly found in the documents despite the importance of the topic, especially for formulated products 143 .…”
Section: Resultsmentioning
confidence: 99%
“…For example, Dutta et al (2003) found that pricing capabilities can be a source of competitive advantage, and noted that firms must invest to develop and maintain the necessary pricing management skills and processes. Chan, Fung, and Ng (2018) summarized four pricing strategies, named as perceived value pricing (based on the value perceived by the customer), penetration pricing (set a lower price at product introduction), skimming pricing (set a higher price when a unique product is first to market), and promotional pricing (offer a lower price for a limited time), to set the price based on product quality and consumer awareness. Liozu (2017) agrees with the view that value-based pricing is a science requiring capabilities proposed by Hinterhuber and Liozu (2012), which relate to customer intimacy and what is critical in their daily operations, market segmentation, competitive analysis, and the ability to extract differentiation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…1,2 In teaching, it is gradually becoming part of the mainstream of chemical engineering as signified by the publication of a number of monographs and textbooks. [3][4][5][6] In research, much has been accomplished in advancing different aspects of product design, which include microeconomics, 7,8 design strategy, 9 design models, 10 and simultaneous product and process design. [8][9][10][11] In addition, a framework that captures the hierarchical, multidisciplinary, and multiscale nature of product design activities has been formulated.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6] In research, much has been accomplished in advancing different aspects of product design, which include microeconomics, 7,8 design strategy, 9 design models, 10 and simultaneous product and process design. [8][9][10][11] In addition, a framework that captures the hierarchical, multidisciplinary, and multiscale nature of product design activities has been formulated. 12 Elements of the framework that include model-based methods, rule-based methods, tools, databases, and experiments have been identified or developed to handle different design tasks.…”
Section: Introductionmentioning
confidence: 99%